The CHEK2 c.1100delC germline mutation rarely contributes to breast cancer development in the Czech Republic - Kleibl, Zdenek; Novotny, Jan; Bezdickova, Drahomira; Malik, Radek; Kleiblova, Petra; Foretova, Lenka; Petruzelka, Lubos; Ilencikova, Denisa; Cinek, Petr; Pohlreich, Petr (Breast cancer research and treatment, 2005)
In this study we performed the CHEK2 c.1100delC mutation analysis in 1046 breast cancer patients and 730 unaffected control individuals. The mutated allele was found in 3 out of 688 unselected sporadic breast cancer patients and in 1 out of 358 familial/early onset breast cancer patients. Two mutations were identified in a cohort of 730 controls. Our results support the finding that frequency of CHEK2 c.1100delC mutation varies among different populations. Based on our results, genotyping of CHEK2 c.1100delC mutation in clinical settings in the Czech Republic could not be recommended.
Keywords: DNA Mutational Analysis; lidé; Middle Aged; Adult; Case-Control Studies; checkpoint kinasa 2; Female; Protein Serine-Threonine Kinases; Germ-Line Mutation; Humans; Breast Neoplasms; nádory prsu; Risk; Breast Neoplasms, Male; protein-serin-threoninkinasy; studie případů a kontrol; Česká republika; lidé středního věku; mužské pohlaví; zárodečné mutace; riziko; Czech Republic; ženské pohlaví; Checkpoint Kinase 2; Male; nádory prsu u mužů; dospělí; mutační analýza DNA